2021
DOI: 10.1002/ange.202109735
|View full text |Cite
|
Sign up to set email alerts
|

Feedback and Communication in Active Hydrogel Spheres with pH Fronts: Facile Approaches to Grow Soft Hydrogel Structures

Abstract: Compartmentalized reaction networks regulating signal processing, communication and pattern formation are central to living systems. Towards achieving life‐like materials, we compartmentalized urea‐urease and more complex urea‐urease/ester‐esterase pH‐feedback reaction networks into hydrogel spheres and investigate how fuel‐driven pH fronts can be sent out from these spheres and regulated by internal reaction networks. Membrane characteristics are installed by covering urease spheres with responsive hydrogel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Previously, we have explored patterning multicomponent gels by acid diffusion, demonstrating it is a powerful approach to generating dynamic multidomain gels with evolving and/or transient spatially resolved characteristics. Although studies in which H + diffusion is used to trigger gelation are increasingly common, very few studies have investigated the diffusion of other active species in order to trigger gel formation. ,, Having demonstrated that CaCl 2 was an effective alternative trigger for multicomponent systems, yielding fully characterized self-sorted multicomponent gels across all length scales, we next decided to explore whether calcium ions could be used as a mild, diffusible trigger to pattern these multicomponent gels. The goal was to achieve spatial and temporal control of Nap-FF assembly by diffusing CaCl 2 within a preformed DBS-CONHNH 2 matrix.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have explored patterning multicomponent gels by acid diffusion, demonstrating it is a powerful approach to generating dynamic multidomain gels with evolving and/or transient spatially resolved characteristics. Although studies in which H + diffusion is used to trigger gelation are increasingly common, very few studies have investigated the diffusion of other active species in order to trigger gel formation. ,, Having demonstrated that CaCl 2 was an effective alternative trigger for multicomponent systems, yielding fully characterized self-sorted multicomponent gels across all length scales, we next decided to explore whether calcium ions could be used as a mild, diffusible trigger to pattern these multicomponent gels. The goal was to achieve spatial and temporal control of Nap-FF assembly by diffusing CaCl 2 within a preformed DBS-CONHNH 2 matrix.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, we wanted to explore the considerable potential of Ca 2+ to create patterned gels (Figure c). There has been emerging interest in shaping and patterning supramolecular gels, , and diffusion can be an effective way of achieving dynamic patterning. , For example, some studies have used H + diffusion to trigger gel assembly with spatial and temporal resolution. We previously achieved spatiotemporally resolved patterning of DBS-COOH and DBS-CONHNH 2 based on acid diffusion. We reasoned that replacing DBS-COOH with Nap-FF may not only raise the p K a value to useful levels but also enable calcium ion diffusion to direct gel assembly, offering a potentially biocompatible method for generating patterned multidomain materials with potential future applications in tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Taylor, Pojman and co-workers used this urease-driven base-releasing hydrogel to initiate a polymerization process in close proximity to the hydrogel . In an elegant study, Walther and co-workers built on this concept, demonstrating that the basic pH waves could assemble a base-responsive LMWG, and in preliminary work, began to pattern these objects …”
Section: Introductionmentioning
confidence: 99%
“…In this new study, inspired by some of the landmark work on propagating pH waves, , and wider interests in the ability of dynamic “fuelled” gel systems to generate spatially resolved systems, we wanted to develop a system in which one supramolecular gel assembled on the surface of another to generate multigelator core–shell systems (Figure ). We reasoned that the growing shell could be used as an “adhesive” to link multiple beads together, and that this could provide access to sophisticated shaped and patterned materialsa process we describe as ‘diffusion-adhesion assembly’.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation